2022
DOI: 10.1186/s12957-022-02650-x
|View full text |Cite
|
Sign up to set email alerts
|

Intercalary allograft reconstruction following femoral tumour resection: mid- and long-term results and benefits of adding a vascularised fibula autograft

Abstract: Purpose Bone healing in femoral reconstructions using intercalary allografts can be compromised in a tumour context. There is also a high revision rate for non-union, infection, and fractures in this context. The advantages and disadvantages of an associated vascularised fibula graft (VFG) are still a matter of debate. Methods In a multicentre study, we retrospectively analysed 46 allograft reconstructions, operated on between 1984 and 2017, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…As a result, this requires multiple revision surgeries, thus amplifying the financial strain on patients and their families. We suggest that for pediatric patients under the age of 8 diagnosed with lower limb osteosarcoma, in cases where oncological factors permit limb preservation and options for artificial implants are limited due to the patient’s young age, biological reconstruction methods such as bone allograft 25 28 and vascularized fiber graft (VFG) 27 , 29 , 30 may improve functional outcomes and a reduced necessity for multiple revision surgeries. Tissue tolerance in pediatric patients increases after the age of 8, thereby making limb salvage surgery using extendable prostheses a viable option.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, this requires multiple revision surgeries, thus amplifying the financial strain on patients and their families. We suggest that for pediatric patients under the age of 8 diagnosed with lower limb osteosarcoma, in cases where oncological factors permit limb preservation and options for artificial implants are limited due to the patient’s young age, biological reconstruction methods such as bone allograft 25 28 and vascularized fiber graft (VFG) 27 , 29 , 30 may improve functional outcomes and a reduced necessity for multiple revision surgeries. Tissue tolerance in pediatric patients increases after the age of 8, thereby making limb salvage surgery using extendable prostheses a viable option.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, the graft survival rates were 74% at 5 years, 60% at 10 years, and 56% at 20 years. Crenn et al reported that the 5-year graft survival rate was 71% after reconstruction using an allograft without a vascularized fibula graft [24]. In another study of allograft reconstruction for the humerus, the 5-year graft survival rate was 71% [25].…”
Section: Discussionmentioning
confidence: 99%
“…The case presented here is one of the few in the literature where the Capanna technique was used in a non-oncologic indication [ 1 , 3 , [9] , [10] , [11] , [13] , [14] , [15] , [16] , [17] , [18] ]. The technique consists in the use of an allograft strut to reinforce cases where vascularized grafts are at a higher risk of fracture or nonunion as a result of chemotherapy [ 11 , 15 ].…”
Section: Discussionmentioning
confidence: 99%